Trends in High-Intensity Statin Therapy After Myocardial Infarction Among U.S. Adults, 2011-2019 - Colantonio, Lisandro (2022)
Fil: Mejía, Raúl M. CEDES. Centro de Estudios de Estado y Sociedad. Área de Salud, Economía y Sociedad; Argentina.